Komitmen Kerja Kepala Madrasah dalam Meningkatkan Efektivitas Madrasah Tsanawiyah Swasta di Kepulauan Riau - Candra Wesnedi; Ahmad Syukri; Kasful Anwar (PT. PENERBIT TIGA MUTIARA, 2024)
This study was conducted to see the work commitment of the Madrasah principal in improving the effectiveness of Private Junior High Schools (MTs) in the Riau Islands. As an effort to improve the quality of education in madrasas, it is hoped that private madrasas can compete with other public schools. This study uses a qualitative approach that describes the object of study through the process of extracting facts and object data in the field. Data collection techniques use interviews, observation and documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions or verification. The results of the study indicate that the work commitment of the Madrasah principal in improving the effectiveness of private MTs in the Riau Islands is not optimal, because there are still many aspects that have not been achieved in terms of realization, budget constraints for the procurement of Madrasah facilities and infrastructure, increasing the professionalism of human resources, and other facilities that are still very limited. For this reason, the head of private MTs in the Riau Islands Province tries to improve the effectiveness of madrasas by implementing strategic educational development concepts. The roles played by the head of the Madrasah are; 1) focusing on common interests, 2) improving communication and understanding, 3) increasing involvement and participation, and 4) avoiding win-lose solutions. These roles are very helpful in realizing increased effectiveness of education in madrasas.